PENGARUH INTERPERSONAL COMMUNICATION DAN PROFESIONAL COMPETENCE TERHADAP EMPLOYEE PERFORMANCE DI MITRA STATISTIK BPS - Rendito Deanova Dwiputra; Asep Gunawan; Dadang Priyono (PT. Hasba Edukasi Mandiri, 2025)
This study aims to examine the effect of interpersonal communication and professional competence on employee performance among field officers (Mitra Lapangan Statistik) at BPS Kabupaten Cirebon. Methodology: A quantitative survey was conducted with 91 field officers selected via purposive sampling. Data were collected using Likert-scale questionnaires measuring Interpersonal Communication (X₁), Professional Competence (X₂), and Employee Performance (Y). Multiple linear regression analysis was employed to test hypotheses. Results: Both interpersonal communication and professional competence had significant positive effects on employee performance: This is among the first studies focusing specifically on non-ASN Mitra Lapangan Statistik performance determinants in Kabupaten Cirebon. Originality: It integrates interpersonal and competence dimensions within a single regression model in a government-survey context.